Response surface methodology-based optimization of Inonotus hispidus’ liquid fermentation medium and evaluation of its exopolysaccharide activities - Gao, Yuhan; Li, Xiaomin; Xu, Hui; Sun, Huijuan; Zhang, Junli; Wu, Xiaoping; Fu, Junsheng (Frontiers in Microbiology, 2024)
Inonotus hispidus, commonly referred to as the Sanghuang mushroom, is a species that is consumed as a tea. To date, this is the only species of the same fungus that has been successfully cultivated. A single-factor test was conducted using Inonotus hispidus MS-5 and MS-9 as test materials. The response surface methodology was adopted to design and optimise the liquid fermentation medium for them. As indicated in the results, the optimum fermentation conditions for MS-5 include 24.09 g/L glucose, 7.88 g/L yeast extract, 0.99 g/L dandelion powder, 1.5 g MgSO4, 2 g KH2PO4, 0.01 g vitamin B1, and 1 L deionized water; the optimum fermentation conditions for MS-9 include 24.64 g/L glucose, 7.77 g/L yeast extract, 0.98 g/L dandelion powder, 1.5 g MgSO4, 2 g KH2PO4, 0.01 g vitamin B1, and 1 L deionized water. Under such conditions, the mycelial biomass (dry weight) values were able to reach 16.02 g/L and 14.91 g/L for MS-5 and MS-9, respectively, which were 1.6 and 1.54 times those measured before optimization. As revealed in the antioxidant and anticancer experiment, Inonotus hispidus exopolysaccharides has corresponding functional effects at the cellular level. This research optimised the liquid culture formulation of Inonotus hispidus and demonstrated that the function of it as a traditional Sanghuang herbal tea is well-documented.